PENGARUH HARD SKILL DAN SOFT SKILL TERHADAP SELF EFFICACY MAHASISWA - Windarini Cahyadiana (Fakultas Psikologi Universitas Wisnuwardhana Malang, 2020)
The purpose of this research is to determine how much influence hardskills and softskills to shaping self efficacy of university student. Because these two skills, can make individuals who have it, feel confident to do an activity and get the results as expected. This research can be classified in classroom action research. The author made observations during the teaching and learning process, and also used a questionnaire to find out the opinions of the respondents. And the results, self management is the variable that plays the biggest role in shaping individual self efficacy. Having self management, means being able to manage themselves and relationships with others.